Impact action of a projectiles on special protective structures and ways to increase their protective capacity - Andrukhiv, A.; Baranov, A.; Huzyk, N.; Sokil, B.; Sokil, M. (Military Technical Collection, 2021)
A method for studying the reaction of elastic elements of protective structures to a series of impact actions of shells has been developed. In the work, the elastic elements of the protective structure are modeled by homogeneous beams, and the dynamic action of the shells is simulated by instantaneous point-applied forces. A mathematical model of this dynamic process is constructed, which is a boundary value problem for a hyperbolic equation with an irregular right-hand side. The latter is described using Dirac delta functions. Cases of both fixed and free ends of protective elements are considered. The main ideas of perturbation methods are used for the researches carried out in the work. Analytical dependences for the description of elastic deformations of a protective element which are basic for definition of its strength characteristics are received. They and the graphical dependences built on their basis for specific cases show that the dynamic deformations of the protective element for the fixed ends are greater in the case of the projectile closer to its middle, at the same time for the free ends – closer to the end. With regard to the modernization of protective structures, the dynamic effect on their elements can be reduced by using elastic reinforcement or changing the method of fixing the ends of the protective element: elastic or with a certain angle of inclination of the bearing surfaces. It is proposed to use special plastics, soil layer, flexible wood flooring, etc. as elastic reinforcement. The technique used in the work is the basis for determining the strength characteristics of protective elements, and from so – to check the reliability of the protective structure; study of the dynamics of protective and similar types of structures, taking into account the nonlinear characteristics of the elastic elements of protective structures; study of more complex oscillations of elements of protective structures. In the case of a series of impacts, it is obvious that the amplitude of deflection of the protective element after each impact will increase over time, because the model does not take into account the force of viscoelastic friction. These tasks will be the subject of further research.